SYNTHESIS OF CR(III) NICOTINATE COMPLEX AT LOW PH - FAJAR ANUGRAH NIM:10513071, MOH.
Cr(III) nicotinate complex is an anti-diabetic mellitus type II suplement that is used since 1980. The Cr3+ ion known as a part of Glucose Tolerance Factor (GTF), a macromolecule that has an ability to increase the insulin activity. The nicotinic acid is used as an antioxidants and able to maintain the condition of human nerve system. The synthesise of Cr(III) nicotinate complexes was studied since 1984. However, those complexes have varying formulas and their structures are not well determined. In this experiment, the complex of Cr(III)-nicotinate was synthesized with molar ratio of Cr3+ : nicotinic acid as 1:3. The pH of the solution was adjusted 3,5-4. Two methods were used on the synthesise of Cr(III) nicotinate in this experiment, i.e the reflux and the reduction methods. The colour of Cr(III) nicotinate complexes formed by those methods were green. The solid state UV-Vis spectra of of Cr(III) nicotinate that was synthesized by the reflux method showed the maximum absorbance at 437 and 581 nm. While the complex produced from the reduction method has the maximum absorbance at 438 and 580 nm. These maximum absorbance were assigned to the transition of 4T1g ? 4A2g and 4T2g ? 4A2g respectively. The coordination bond between Cr(III) ion and the nicotinate ligand was observed in the presence of a shift of carboxylate vibration of the nicotinate ligand in the infrared spectrum. The complexes produced by the reflux and the reduction methods showed the shift of carboxylate vibration of the nicotinate ligand as 44 cm(rumus)1 and 77 cm(rumus)1, respectively. The mass spectra showed that the Cr(III) nicotinate complexes were a cation, with the molecular formula [Cr2(Hnic)(nic)4(OH)(CH3OH)2]+ (m/z 860) for the reflux method and [Cr(Hnic)(nic)(OH)(H2O)2(CH3OH)]+ (m/z 381,8) for the reduction method. These complexes were paramagnetic with the magnetic moments of 3,74 and 3,78 ?B respectively. The result of AAS method showed that both complexes have Cr with percentage 15% and 18,75% respectively. The characteristic results showed that the two complexes produced in this experiment have different molecular formulas, i.e the dimer molecule produced by the reflux method and the monomer molecule produced by the reduction method.